The Implementation of Window Shopping Method Innutrition Science Course - Syaifudien, Muhammad Asyrof; Patriasih, Rita; Juwaedah, Ade (Universitas Pendidikan Indonesia (UPI), 2024)
The learning method is a way for educators to present learning materials as an effort to achieve learning objectives. In the learning process, educators find various problems, one of which is the lack of student participation in the learning process. So there needs to be an effort to develop learning methods to increase student participation. One of the learning methods that focuses learning on students is the windows shopping method. This research is a descriptive qualitative research using a one group pretest-posttest type design. Data collection uses documentation, observation, tests and field notes. The results showed that the participation of students in the learning process using window shopping showed that they participated in learning. The participation of students begins to be seen when the teacher provides a stimulus for activities from the beginning of learning to the end of learning and shows a change in the competence of students' knowledge. In future research, it is hoped that it can be carried out using a treatment class and a control class and several cycles are carried out.